Misi dalam Doa Yesus Menurut Yohanes 17 - Johannis Siahaya (JURNAL TERUNA BHAKTI, 2019)
Jesus came into the world with a "mandate" special of the Father in Heaven, seeking and saving the lost. As an envoy mission of the eternal kingdom of heaven, Jesus becomes the "owner", and "implementing" the mandate of the Father for approximately three years in his work on earth. One way of doing mission by is through prayer. Prayer is a powerful weapon that should be possessed by any Christian or for those who would be the envoy's mission. Abstrak Yesus datang kedalam dunia dengan membawa ”mandat” khusus dari Bapa di Sorga, yakni mencari dan menyelamatkan yang hilang. Sebagai seorang utusan misi dari Kerajaan Sorga yang kekal, Yesus menjadi ”pemilik”, sekaligus ”pelaksana” mandat dari Bapa selama kurang lebih tiga tahun dalam karyaNya di bumi. Salah satu cara melakukan misi oleh adalah melalui doa. Doa adalah senjata ampuh yang seharusnya dimiliki oleh setiap orang Kristen atau bagi mereka yang akan menjadi utusan misi.